Regional Characteristics of Human Resources in Hungary During the Transition - Rechnitzer, János; Smahó, Melinda (Discussion Papers, 2012)
The objective of regional development policies in the modern economies is the decrease of the disparities in the living conditions of the population. The interventions of the regional policies aim at the transformation of the economic sectors, the increase of the employment possibilities and the improvement of the different infrastructural and institutional conditions having an impact on the living conditions. The focus of the efforts is to guarantee possibilities by the renewal of the spatial factors promoting development and by the safeguarding of the conditions for a catching up. This latter factor serves spatial equalisation and the moderation of the regional disparities, the effects of which of course can only be felt in the long run. Work culture and the and culture of activities show definite regional characteristics, the accumulated experiences show different levels of activity, thus the adaptation to the new skills is very much differentiated in space, just because of these social and cultural correlations (Hahne, 1985). The former paradigm of regional development - import of the factors of production, top-down controlled transformation with a predominantly economic view - was questioned and replaced by a new way of thinking and action. This new, shaping paradigm has two central elements: the first is bottom-up approach; the second - basically connected to and deriving from the first - is the activation of the human resources, the promotion of its basic elements. The first part of our study focuses on the new factors of regional development, including the elements generated by the human resources. The subsequent chapters deal with the regional structure of a few dimensions of human resources, demonstrating the regional characteristics that have stabilised or emerged in the 1990s and nowadays. Finally we summarise the characteristic features, implying the trends of regional development and thus the presumed methods of the activation of human resources.